2010
DOI: 10.1007/s00018-010-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A4 interacts with the NF-κB p50 subunit and modulates NF-κB transcriptional activity in a Ca2+-dependent manner

Abstract: Previously, we identified annexin A4 (ANXA4) as a candidate substrate of caspase-3. Proteomic studies were performed to identify interacting proteins with a view to determining the roles of ANXA4. ANXA4 was found to interact with the p105. Subsequent studies revealed that ANXA4 interacts with NF-kappaB through the Rel homology domain of p50. Furthermore, the interaction is markedly increased by elevated Ca(2+) levels. NF-kappaB transcriptional activity assays demonstrated that ANXA4 suppresses NF-kappaB transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 32 publications
(49 reference statements)
0
60
1
1
Order By: Relevance
“…It has been shown to have numerous other cellular functions including cell division, Ca 2ϩ signaling, growth regulation and inflammation (83), and to colocalize on cell membrane surfaces (84), which may indicate a role in the reaction to physical stress. It also plays an important role in modulating the NF-B signaling pathway (85), which is important in regulating numerous genes involved in the immune response, cell proliferation, differentiation, survival, and apoptosis (86,87). FIG.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to have numerous other cellular functions including cell division, Ca 2ϩ signaling, growth regulation and inflammation (83), and to colocalize on cell membrane surfaces (84), which may indicate a role in the reaction to physical stress. It also plays an important role in modulating the NF-B signaling pathway (85), which is important in regulating numerous genes involved in the immune response, cell proliferation, differentiation, survival, and apoptosis (86,87). FIG.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge this is the first report regarding change in annexin A4 expression status in ESCC while for other cancers such as clear cell carcinoma of ovary (Kim et al, 2010), colorectal carcinoma and gastric cancer (Duncan et al, 2007;Lin et al, 2008a) over-expression was observed. Annexin A4 was reported to modulate NF-κB signaling pathway (Jeon et al, 2010) which also depends on its interactions with p50 and intracellular calcium ion level. In addition annexin A4 plays role in metastasis and confers anticancer drug resistance (Duncan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Two shared human vascular addresses were found by our selection. First, ANXA4, a membrane protein identified in Ca þ2 -dependent membrane trafficking (30), was characterized as a marker of the human vasculature that interacts with α4 integrins. Among the α4 integrin family, α4β1 (31) and/or α4β7 (32) are membrane constituents of leukocytes that mediate cell adhesion to the vascular endothelium and affect inflammation, immune response, and tumor dissemination (31).…”
Section: Discussionmentioning
confidence: 99%